2010
DOI: 10.1111/j.1745-4514.2009.00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Related Anticancer Activity of Flavonoids: Involvement of Reactive Oxygen Species Generation

Abstract: The cytotoxicity and apoptosis induction effect of 23 flavonoids on human leukemia cells (HL‐60) were investigated. 3,6‐Dihydroxyflavone, luteolin and geraldol showed the most potent cytotoxic effect. By comparing the cytotoxicity of selected molecules that differ in only one structure element, we identified several structural properties important for potent cytotoxic activity, including the presence of 2,3‐double bond, appropriate hydroxyl numbers, 3‐OH and ortho‐OH in ring B. Flavonoids with a 5‐OH exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Its pronounced free radical scavenging ability is due to its polarity and number of conjugated double bonds. Among the dietary flavonoids, 3,6-dihydroxyflavone is ubiquitously present in the vegetables and fruits and exhibit strong antioxidant properties (Chang et al 2010). Dietary supplement, selenium methyl selenocysteine, exhibits significant protection against an oxidative insult (Susana 2007) and facilitates cell damaging free radical in the body (Rooseboom et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Its pronounced free radical scavenging ability is due to its polarity and number of conjugated double bonds. Among the dietary flavonoids, 3,6-dihydroxyflavone is ubiquitously present in the vegetables and fruits and exhibit strong antioxidant properties (Chang et al 2010). Dietary supplement, selenium methyl selenocysteine, exhibits significant protection against an oxidative insult (Susana 2007) and facilitates cell damaging free radical in the body (Rooseboom et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor incidence in the MNU + 20 mg/kg 3,6-dihydroxyflavone (3,6-DHF) treatment group was significantly lower than that in the MNU-only treatment group, indicating that oral administration of 3,6-DHF (20 mg/kg/day) can effectively suppress MUN-induced mammal carcinogenesis. strong cytotoxicity against breast cancer cells and a stronger anticancer activity in vitro than apigenin, genistein, quercetin, luteolin, and so forth [16][17][18]. In the present study, we investigated the anticancer effect of 3,6-DHF in vivo.…”
Section: Discussionmentioning
confidence: 94%
“…Several previous studies demonstrated the potential in vitro anticancer activity of flavonoids in diverse cell systems . Particularly, apigenin and luteolin exhibited significant antiproliferative properties against various cancer cell lines, including human thyroid cancer cells . Vicenin‐2 showed antiproliferative, anti‐angiogenic, and pro‐apoptotic effects on carcinoma of prostate cells .…”
Section: Resultsmentioning
confidence: 97%